RNA-Seq-based transcriptome analysis of methicillin-resistant Staphylococcus aureus growth inhibition by propionate - Im, Jintaek; Lee, Dongwook; Park, Ok-Jin; Natarajan, Sathishkumar; Park, Junhyung; Yun, Cheol-Heui; Han, Seung Hyun (Frontiers in Microbiology, 2022)
Staphylococcus aureus is a pathogen that causes a variety of infectious diseases such as pneumonia, endocarditis, and septic shock. Methicillin-resistant S. aureus (MRSA) evades virtually all available treatments, creating the need for an alternative control strategy. Although we previously demonstrated the inhibitory effect of sodium propionate (NaP) on MRSA, the regulatory mechanism of this effect remains unclear. In this study, we investigated the regulatory mechanism responsible for the inhibitory effect of NaP on MRSA using RNA-Seq analysis. Since the growth of MRSA was initially inhibited by NaP at 3 h, this time point was chosen for RNA-Seq analysis for MRSA treated with NaP. A total of 171 differentially expressed genes (DEGs) with log2 fold change ≥ 2 and P < 0.05 was identified in the NaP treatment group compared with the control group. Among these 171 genes, 131 were up-regulated and 40 were down-regulated. Upon gene ontology (GO) annotation analysis, total 26 specific GO terms in “Biological process,” “Molecular function,” and “Cellular component” were identified in MRSA treated with NaP for 3 h, respectively. “Purine metabolism”; “riboflavin metabolism”; and “glycine, serine, and threonine metabolism” were identified as major altered metabolic pathways among the eight significantly enriched KEGG pathways in MRSA treated with NaP. Furthermore, the MRSA strains deficient in purF, ilvA, ribE, or ribA, which were the up-regulated DEGs in the metabolic pathways, were more susceptible to NaP than wild-type MRSA. Collectively, these results demonstrate that NaP attenuates MRSA growth by altering its metabolic pathways, suggesting that NaP can be used as a potential bacteriostatic agent for prevention of MRSA infection.